The Scope and Definitions of Heritage: From Tangible to Intangible - Yahaya, A. (Taylor & Francis, 2006)
Since the adoption of the Venice Charter in 1964, there have been many conservation guidelines in the form of charters, recommendations and resolutions that have been introduced and adopted by international organisations such as UNESCO and ICOMOS. This article focuses on the scope and definition of heritage as promulgated by the various charters across the globe. The term ‘historic monument’ used in the Venice Charter 1964 was reinterpreted by ICOMOS in 1965 as ‘monument’ and ‘site’; and by UNESCO in 1968 as ‘cultural property’ to include both movable and immovable. The different terminology between the UNESCO and ICOMOS was reconciled at the World Heritage Convention 1972. At national and regional levels the scope of heritage was broadened to include gardens, landscape and environment, and later reinterpreted and defined quite differently in Europe, Australia, New Zealand, Canada and China. Although the scope of heritage, in general, is now agreed internationally to include ‘tangible’ and ‘intangible’ as well as ‘environments’, the finer terminology of ‘heritage’ has not been streamlined or standardised, and thus no uniformity exists between countries.